1954
DOI: 10.1177/003591575404700313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology

Abstract: The Speaker started by paying tribute to Walter Ernest Dixon, in whose honour these lectures are given at intervals of three years (Gunn, 1932; Dale, 1935).Pharmacological experiments on human beings started when the first medical man treated his first patient, for all good doctors are really doing experiments all the time. No two patients are quite alike and it is often necessary to find out by experiment what treatment suits each individual patient. The results of such experiments are stored up in the memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

1960
1960
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…1961) commented:`S tatistics and certain concepts, such as double blind trial, are on everyone's mind today F F F '' Any history of the double blind test should include the history of the placebo since it is an integral part of the procedure. Gaddum (1954) was not in agreement with the use of the term placebo. Referring to the double blind test, he stated:`I t generally involves giving the controls dummy treatment which cannot be distinguished from the real treatment.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…1961) commented:`S tatistics and certain concepts, such as double blind trial, are on everyone's mind today F F F '' Any history of the double blind test should include the history of the placebo since it is an integral part of the procedure. Gaddum (1954) was not in agreement with the use of the term placebo. Referring to the double blind test, he stated:`I t generally involves giving the controls dummy treatment which cannot be distinguished from the real treatment.…”
mentioning
confidence: 78%
“…In a review lecture on clinical pharmacology, Gaddum (1954), at the University of Edinburgh, stated:`E rrors of assessment may occur when the results of the treatment are assessed by someone who may be too hopeful or too sceptical F F F One method of avoiding this type of error is to depend entirely on objective measurements of such things as temperature or weight. This is seldom very satisfactory, and it seems a pity to pay no attention at all to the doctor's opinion or to the patient's opinion.…”
mentioning
confidence: 99%
“…In order to assess the effect of the administration of medication, the administration of inactive compounds is compared with that of active compounds. Gaddum (1954) has suggested that the term 'dummy tablet' should be used for the inactive medication; he points out that the word placebo means a medicine given more to please than to benefit the patient. He defines a dummy tablet as a counterfeit object which is intended to have no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Gaddum (32) vermutet, daß die Beobachtungen von Lind aus dem Jahre 1747 als früheste Nutzanwendung von Plazebos (dort Leerpräparate genannt) anzusehen sind. Der erste systematische und experimentell kontrollierte Einsatz von Plazebos geschah wahrscheinlich 1933 durch Diehl (19), der Plazebos zur Kontrolle vorbeugender Mittel gegen Schnupfen verwendete.…”
Section: Plazebos Als Norm Der Wissenschaftlichen Medizinunclassified